Analisis Perlindungan Hukum Merek Terkenal Dari Tindakan Pendaftaran Merek yang Beriktikad Tidak Baik (Studi Kasus : Sengketa Merek “STARBUCKS” Kopi Vs “STARBUCKS” Rokok) - Putri, Hirdina Sartika Dwi Yunita Amelia; Dewanto, Wishnu (LITERATUS, 2026)
The rapid development of the global economy has made trademarks one of the main instruments in maintaining business reputation and identity. However, in practice, the phenomenon of trademark registration in bad faith has emerged, leading to disputes between well-known trademark owners and other parties attempting to exploit the reputation of such trademarks. The formulation of this research examines how the juridical criteria of well-known trademarks (Article 21 paragraph (1) letter b) and the criteria of bad faith (Article 21 paragraph (3)) are concretely implemented by judges of the Commercial Court in deciding trademark disputes, as well as the extent of the effectiveness of legal protection provided by Law Number 20 of 2016 concerning well-known trademarks against bad faith trademark registration practices, and the recommendations for improving the relevant regulations. This research employs a normative juridical method with statutory, conceptual, and case approaches. The results of the study indicate that the application of the criteria for well-known trademarks and bad faith by judges of the Commercial Court has moved towards a progressive and contextual approach, where judges not only assess the formal aspects of trademark registration but also consider global reputation, substantive justice, and consumer protection. Nevertheless, the effectiveness of legal protection for well-known trademarks in Indonesia still faces challenges in terms of proving reputation and identifying indicators of bad faith within trademark administrative practices. Therefore, this research recommends regulatory improvements through the clarification of the criteria for well-known trademarks and bad faith, strengthening coordination between the Directorate General of Intellectual Property and the courts, as well as the application of the principle of good faith as a foundation